Diversity of ornamental trees from Amravati city of West Vidarbha region - N, Pawade P; Rothe, S P (Recent Research in Science and Technology, 2012)
The present study deals with the diversity of ornamental trees from Amravati District of West Vidarbha region of Maharashtra. All these ornamental trees show diversity in their habitat, floral structure, flowering period, etc. In the present investigation, extensive field surveys were conducted in the different localities of Amravati district during 2005-2011containing description, distribution, origin, vegetative and flowering period of 25 ornamental trees species from 19 families with their photographs and preserved as Herbaria.